Guide to Assessment Scales in Bipolar Disorder - Vieta, Eduard. (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2010)
A guide to the recent developments in the assessment of bipolar disorder written by respected authors in the field of psychiatry Written for psychiatrists, clinical researchers, mental health nurses and other healthcare professionals who use rating scales in clinical practice Provides rating scales that can be used for the systematic evaluation of patients in standard clinical practice The evidence base in each chapter has been expanded and brought fully up-to-date Schizophrenia is a chronic disease encompassing a range of symptoms including hallucinations, delusions and social withdrawal. Different measurement tools are utilized to assess the symptoms of schizophrenia. The previous two editions of the Guide to Assessment Scales in Schizophrenia are now outdated and no longer clinically correct so this completely new edition written by a new team of leading clinicians and researchers brings you fully up to date with recent developments.